2020
DOI: 10.4103/jhrs.jhrs_143_19
|View full text |Cite
|
Sign up to set email alerts
|

Isolated fallopian tube torsion: A rare twist with a diagnostic challenge that may compromise fertility

Abstract: Isolated Fallopian tube torsion (IFTT) is a rare entity with utmost important gynecological emergency with difficult preoperative diagnosis. Our aim is to analyze the clinical presentation, risk factors, and management of IFTT. We retrospectively analyzed all patients with intraoperative diagnosis of IFTT in our endogynecological department over a time period of 3 years and 6 months (January 2015–June 2018) in a tertiary level laparoscopic center. The clinical profile of the patients was analyzed and the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Hence, whenever we encounter an adnexal torsion, IFTT should be in patients with a previous history of tubal ligation, with an elongated cystic mass, who have a sudden onset of abdominal pain or pelvic pain. 4 Timely intervention in the form of surgery may salvage the fallopian tube in case fertility is desired and prevent other sequel of torsion even if fertility is not desired. Laparoscopy is preferred as it is minimally invasive and it also helps in diagnosis of any other pathology and operative intervention at the same time if needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, whenever we encounter an adnexal torsion, IFTT should be in patients with a previous history of tubal ligation, with an elongated cystic mass, who have a sudden onset of abdominal pain or pelvic pain. 4 Timely intervention in the form of surgery may salvage the fallopian tube in case fertility is desired and prevent other sequel of torsion even if fertility is not desired. Laparoscopy is preferred as it is minimally invasive and it also helps in diagnosis of any other pathology and operative intervention at the same time if needed.…”
Section: Discussionmentioning
confidence: 99%
“…Devi et al suggested that most of the torsions are noted in the distal two-third of the tube, and believed that the complete salpingectomy is better than partial whenever it is necessary because the proximal nonfunctional part of the tube can be a site of ectopic pregnancy or reformation of hydrosalpinx if it gets occluded and removal of only ampulla and fimbria and keeping the nonfunctional portion is of no use and may increase the risk of recurrence. 4…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Some suggest that hydrosalpinx, which can appear after IFTT, could impair fertility more than salpingectomy itself. (10,11,12) It is not clear whether IFTT is as rare as reported in literature, or if it is widely under-diagnosed. In any event, it seems that under-diagnosis may lead to late laparoscopy possibly affecting future fertility.…”
Section: Postponementmentioning
confidence: 99%
“…Presenting symptoms of isolated torsion of the fallopian tube include acute onset of lower abdominal pain accompanied by nausea, vomiting, and peritoneal signs [7] . It is important in immediate diagnosis and treatment to maintain the fallopian tube [8] . There are many case report about isolated tubal torsion, including Kolovos, Antoniu, Kardakis, Toyoshima, Gross, Raziel that are different from our case [3,7,[9][10][11] , because in this case, Isolated torsion of the left tube occurs without any abnormality and pathology.…”
Section: Introductionmentioning
confidence: 99%